Evaluation of total phenolic content, free radical scavenging activity and phytochemical screening of different extracts of Averrhoa bilimbi (fruits) (International Current Pharmaceutical Journal, 2013)
The present study was designed to investigate the phytochemical screening, the free radical scavenging activity and to determine the total phenolic content of methanolic extract and different solvent soluble fractions of Averrhoa bilimbi Linn. (Oxalidiaceae) fruits. The free radical scavenging activity was evaluated by analyzing the bleaching rate of 1,1-diphenyl-2-picrylhydrazyl (DPPH), and total phenolic content was determined by using Folin-Ciocalteau reagent, which results were expressed in gallic acid equivalent (mg of GAE/g of sample). The phytochemical screening revealed the potent source of different phytochemical constituents on different extractives including, phenol, flavonoid, tannin that are responsible for antioxidant action. In the determination of total phenolic content, different extractives showed a significant content of phenolic compounds ranging from 50.23-68.67 mg of GAE/g of extractive. The plant sample displayed significant DPPH free radical scavenging activity with highest IC50 value in crude methanolic extract (30.365 ?g/ml) followed by chloroform, carbon tetrachloride, pet-ether and aqueous soluble fractions having value of 32.852 ?g/ml, 36.708 ?g/ml, 50.35 ?g/ml, and 79.918 ?g/ml, respectively as opposed to that of the scavenging effects of BHT of 19.656 ?g/ml.DOI: http://dx.doi.org/10.3329/icpj.v2i4.14058 International Current Pharmaceutical Journal, March 2013, 2(4): 92-96